Karya Tari Jejak Kaba Interpretasi Perjuangan Seorang Seniman Rabab dalam Mempertahankan Tradisi Rabab - Alsafitro Alsafitro; Susasrita Loravianti; Wahida Wahyuni; Kurniadi Ilham (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work Jejak Kaba is inspired by the struggle of a Tukang Rabab, portraying the strong fighting spirit possessed by traditional artists, as well as their determination to preserve the roots of traditions passed down through generations and the ways they strive to survive. This becomes the creator’s main focus in highlighting the resilience and perseverance of a traditional Rabab artist, who regards Rabab not merely as a form of entertainment but as a way of life—both as a means of livelihood and as a medium for inheriting traditional art.The creation of this work is realized by emphasizing the space of memory surrounding struggle, sincerity, challenges, anxiety, and loyalty of a traditional artist in maintaining the existence of Rabab tradition amid the rapid changes of the modern era.This work applies Alma M. Hawkins’ choreographic approach as outlined in the book Creating Through Dance and Choreography: Form, Technique, and Content, which consists of several stages: data collection and field observation, exploration, improvisation, formation, and evaluation. The work is further strengthened by the use of lighting to represent atmospheres of calmness, tension, and gloom. Jejak Kaba employs a dramatic type of dance and is performed on an arena stage at the Boestanol Arifin Adam Auditorium.